Solanum Nigrum Linn: An Analysis Of The Medicinal Properties Of The Plant (Journal of Pharmaceutical Negative Results, 2023)
Solanum nigrum linn. is a member of the Solanaceae family since it is often used to treat a broad range of infectious disorders that may harm humans. These herbs not only possess beneficial medicinal characteristics, but they also mitigate the potential side effects of some medications. In addition, they possess beneficial therapeutic characteristics. Because it is an edible sort of plant, several Indian cultures use it as a food supply. This chemical has been used to effectively treat a variety of cancers, as well as acute nephritis, leucorrhea, sore throats, toothaches, dermatitis, and eczema. It has been shown that the Solanum nigrum plant has around 188 distinct chemical components that may be separated from one another. In decreasing order of significance, the four most essential bioactive components included within these chemical compounds are referred to as "steroidal saponins," "alkaloids," "phenols," and "polysaccharides," respectively. As part of the scope of this study, we investigated the pharmacological processes carried out by the Solanum nigrum plant and developed a thorough list of its pharmacological applications in order to get a knowledge of a medicinal component with a broad variety of possible applications.